Long-Term Fine Particulate Matter (PM2.5) Trends and Exposure Patterns in the San Joaquin Valley of California - Ricardo Cisneros; Donald Schweizer; Marzieh Amiri; Gilda Zarate-Gonzalez; Hamed Gharibi (Atmosphere)
Since 1989, California pollution control efforts have caused annual PM2.5 averages to decrease. Despite the decline in ambient air concentrations of PM2.5, the San Joaquin Valley (SJV) of California continues to violate the federal standard for PM2.5. This study evaluated PM2.5 trends, diurnal and seasonal patterns, pollution sources, and air quality improvements from 2000 to 2022 in the SJV. Hourly and daily PM2.5 data from CARB and EPA-certified monitors were analyzed using regression models, polar plots, and Air Quality Index (AQI) classification methods. Monthly PM2.5 concentrations peaked in winter (November–January) and during commute periods, with higher levels observed on Fridays and Saturdays. In this study, the highest daily PM2.5 levels observed in Fresno and Bakersfield occurred during the autumn, most likely due to agricultural activities and higher wind speeds, with daily values greater than 25 µgm−3 and 50 µgm−3, respectively. In contrast, in Clovis, the highest daily PM2.5 concentrations occurred in the winter during episodes characterized by low wind speeds, with values greater than 22 µgm−3. While PM2.5 has declined since 1999, progress has slowed significantly since 2010. However, all sites exceeded the new EPA standard of 9 µgm−3. Without substantial changes to emission sources, meeting federal standards will be difficult.